An Efficient Route to Symmetrical and Unsymmetrical Disulfide, Thioether, and Hydrocarbon Cyclophanes. Issue 43 (19th October 2020) - Phan, Ngoc‐Minh; Shear, Trevor A.; Zakharov, Lev N.; Johnson, Darren W.
Abstract : The union of metal‐directed self‐assembly, dynamic covalent chemistry, and sorting gives rise to 3 new unsymmetrical tetrameric disulfide macrocycles. Stepwise sulfur extrusion from the self‐assembled disulfides to, first, thioethers, and then to hydrocarbons by photochemically promoted routes, gives rise to a collection of 7 new thioether and hydrocarbon cyclophanes related to the venerable family of [ n ]paracyclophanes. These methods provide an efficient self‐assembly approach to the synthesis of hydrocarbon macrocycles (related to carbon "nanohoops"), a class of structures that are typically formed in lengthier, stepwise syntheses. Abstract : We showcase a 3‐step approach – supramolecular self‐assembly, covalent capture, and photochemical sulfur extrusion – to generate a series of disulfide, thioether, and hydrocarbon cyclophanes. An added sorting step allows isolation of unsymmetrical "social sorted" disulfide products, which are converted to hydrocarbon analogs of [2, 2, 2]paracyclophane featuring both phenyl and biphenyl linkers.